Der Berufsstrukturwandel der Beschäftigung in Österreich 1991-2012 - Mesch, Michael (Wirtschaft und Gesellschaft, 2014)
Between 1991 and 2012 the occupational structure of the labor force in Austria shifted significantly towards high-skilled white-collar occupations. Professionals, technicians and associated professionals, and managers already constitute almost 40% of the labor force. The very strong employment shift towards professionals, technicians and associated professionals is interpreted as unambiguous evidence of structural change in the direction of knowledge-intensive and human capital-intensive service and manufacturing activities. Within the tertiary sector knowledge-intensive market and public service industries gained shares of employment, and in manufacturing the structural change of employment favored high-technology and medium high-technology industries. Applying shift-share-analysis it is shown that within industry occupational shifts contributed somewhat stronglier than between industries shifts to the aggregate changes in the occupation-industry-matrix of the labor force. The shifts towards high-skilled white-collar occupations and mid-skilled, interactive white-collar occupations and away from mid-skilled white-collar occupations carrying out routine clerical tasks as well as away from mid-skilled and low-skilled blue-collar occupations in the last decade is consistent with the refined theory of technical progress provided by the “routinization”-hypothesis advanced by Autor et al. (2003): computers and other ITequipment complement both high-skilled non-routine analytical tasks and mid-skilled nonroutine interactive tasks, but substitute for mid-skilled routine cognitive tasks and for midskilled and low-skilled routine manual tasks.